Mass Transport of Uranium During Recharge of Surface Water to Contaminated Groundwater - (:unkn) unknown (My University, 2022)
This study characterized the predominant mass transport mechanisms of uranium during river water recharge to contaminated groundwater to better characterize its mobility. It was hypothesized that the mass transfer of uranium from the solid phase to the aqueous phase was occurring during periods of river water to groundwater recharge via concentration-driven desorption. Sediment data confirmed the presence of uranium on the solid phase via nitric acid extraction. The recharge of river water to the saturated zone of a uranium-contaminated aquifer was simulated in a multi-well tracer test. The injection fluid was Little Wind River water and was traced with added solutes that included a halide and a benzoate to characterize the mass transport mechanisms of uranium. The sampling fluid was a river water/groundwater mix and was analyzed for uranium and artificial and natural tracers. The tracer results suggested that matrix diffusion was likely negligible as evident by the nearly identical breakthrough curves of the halide and benzoate. The measured concentrations of uranium did not exceed the expected concentrations of uranium, resulting in a recovery factor of nearly one; this suggested that the recharge of river water to groundwater did not mobilize uranium. However, the data indicated that redox reactions did occur, specifically, manganese (Mn(II)) and ferrous iron (Fe(II)) were oxidized by oxygen (O2), resulting in recovery factors substantially less than one. These results suggested that reduced species of uranium, such as uraninite (UO2), were likely not present in the saturated aquifer materials because oxidation of U(IV) by O2 is thermodynamically favorable as compared to Fe(II) and Mn(II). Therefore, both matrix diffusion and oxidative dissolution were ruled out as potential mass transport mechanisms of uranium. Thus, the most likely mass transport mechanism of uranium from the solid phase to aqueous phase is desorption, yet this process appears to not be concentration driven. Therefore, it is conceivable that other factors, such as pH, play an important role in the desorption of uranium.
Keywords: Uranium